On the Treatment of Soil Water Stress in GCM Simulations of Vegetation Physiology - Vidale, P. L.; Egea, G.; McGuire, P. C.; Todt, M.; Peters, W.; Müller, O.; Balan-Sarojini, B.; Verhoef, A. (Frontiers in Environmental Science, 2021)
Current land surface schemes in weather and climate models make use of the so-called coupled photosynthesis–stomatal conductance (A–gs) models of plant function to determine the surface fluxes that govern the terrestrial energy, water and carbon budgets. Plant physiology is controlled by many environmental factors, and a number of complex feedbacks are involved, but soil moisture control on root water uptake is primary, particularly in sub-tropical to temperate ecosystems. Land surface models represent plant water stress in different ways, but most implement a water stress factor, , which ranges linearly between  =1 for unstressed vegetation and  = 0 at the wilting point, depending on soil moisture content, "θ" .  is most commonly used to either limit A or gs, and hence carbon and water fluxes, and the research question is whether these treatments are interchangeable. Following Egea et al. (2011) and Verhoef and Egea (2014), we have implemented new  treatments, reflecting higher levels of biophysical complexity in a state-of-the-art land surface model, JULES, by allowing root zone soil moisture to limit plant function non-linearly via individual routes (carbon assimilation, stomatal conductance, or mesophyll conductance) as well as any non-linear combinations thereof. The impacts of our model developments are mostly reflected in predictions of GPP and soil moisture evolution, both in terms of climate means and response to the European 2003 heat wave. Treatments allowing stomatal and mesophyll routes for  effects on vegetation fluxes are better capable to simulate the spatiotemporal variability in water use efficiency during the growing season and can support more versatile ecosystem responses, e.g. those observed in regions that are radiation limited or water limited. We conclude that current practice in weather and climate modelling is inconsistent, as well as too simplistic, failing to credibly simulate vegetation response to soil water stress across the typical range of variability that is encountered for current European weather and climate conditions, including extremes. A generalized approach performs better in current climate conditions and, based on response to extremes, more trustworthy for predicting the impacts of climate change.